Xylem Hydraulic Properties of Five Pinus Species Grown in Common Environment Vary From Needles to Roots With Needle Length and Native‐Range Climate - Wang, Na; Domec, Jean‐Christophe; Palmroth, Sari; Maier, Christopher A.; Xie, Lulu; Yin, Chunying; Chen, Ya‐Jun; Oren, Ram (Plant, cell and environment, 2025)
Plant hydraulics govern water transport linking root to mesophyll surfaces, affecting gas‐exchange, survival and growth. Xylem and leaf structural and functional characteristics vary widely among Pinus species, even when growing under similar conditions. We quantified the variation of xylem anatomy, hydraulic function, and within‐tree hydraulic resistivity distribution, among five widely ranging southern US species: Pinus echinata , Pinus elliottii , Pinus palustris , Pinus taeda and Pinus virginiana . We found that, across species, needle length (NL) explained most of the variation in needle hydraulic properties. Resistivity to water flow in needles through tracheids' bordered‐pits decreased linearly from ~99% to 8% with increasing NL; total tracheid resistivity in branches and roots was partitioned between bordered‐pits and lumens similarly regardless of NL. Mean annual precipitation typical of the species' climatic range (CR) accounted for the variation in root hydraulic properties. Despite strong root‐to‐branch correlations of several attributes, neither NL nor CR explained the variation of any branch attribute. The results suggest that NL dominates needle xylem anatomy and function in a manner consistent with increasing hydraulic efficiency with NL, but CR produces genetic differences resulting in increased resistance to more negative xylem pressures with decreasing precipitation, at a cost of reduced hydraulic efficiency. We quantified the variation of xylem anatomy and within‐tree hydraulics resistivity distribution among five contrasting Pinus species. Needle length structure and function were strongly related to increasing hydraulic efficiency, but genetic control over the development of root xylem was evident.